Aesthetics, performativity and resistance in the narratives of a computer programming community. - Case, Peter; Piñeiro, Erik (Human Relations, 2006)
This article reports on an empirical study of a computer programmer community, focusing on online exchanges in which participants discuss the aesthetics of coding. Naturalistic data were collected during a 12-month period of non-participant observation of the software community in question. The authors estimate that approximately 200 participants are represented in the main dataset. Narrative data are presented under two interpretative rubrics: ‘programmer performatives’ and ‘commercial performativity’. We seek to demonstrate that there is the online equivalent of a great deal of intricate ‘face work’ that programmers do in their narrative exchanges. In expressing and conforming to a ‘hacker ethic’, programmer narratives simultaneously evince technical, ethical and aesthetic motives. There is frequent articulation of resistance and subversive intent expressed toward representatives of employers and employing organizations. Software engineers are acutely aware of the facets of organizational control and demands for performativity that they feel compromise their artistic endeavours. Programmers make sense of their condition ideologically both through their practical pursuit of coding ideals and by espousing a hacker ethic that legitimates their passionate engagement with coding tasks. Reprinted by permission of the publisher.